Literary Journalism, Transdisciplinarity and Complexity Field: The Journalistic and Literary Knowledges of João Guimarães Rosa - de Castro, Gustavo; Dravet, Florence Marie; Vianna, Andrea Jubé; Cruzeiro, Victor Lemes (Brazilian journalism research, 2018)
This article seeks to situate Literary Journalism as a discipline of complex and transdisciplinary knowledge, necessary for the training of every journalist. It seeks to understand and integrate the practice of narration to the problems of the levels of reality. The concepts of Literature of Complexity and Transdisciplinarity serve as a basis for our reflection. With the short story “Com o vaqueiro Mariano”, we bring the literature of João Guimarães Rosa and his relations with journalistic knowledge, from the notion of interview, through the system of production and circulation of information to the techniques of verification that the author used. Finally, we conclude that Literary Journalism allows not only to situate journalism in the communication circuit, but also, and in an extended way, broaden the communication circuit to its cultural dimension, exercising such a pedagogical role relevant to any area of knowledge. Este artigo busca situar o jornalismo literário enquanto disciplina de saberes complexos e transdisciplinares, necessária à formação de todo jornalista. Busca entender e integrar a prática da narração aos problemas dos níveis de realidade. Os conceitos de literatura de complexidade e de transdisciplinaridade servem de base à nossa reflexão. Com o conto “Com o vaqueiro Mariano”, trazemos a literatura de João Guimarães Rosa e suas relações com os saberes jornalísticos, desde a noção de entrevista, passando pelo sistema de produção e circulação da informação até as técnicas de apuração que o autor empregava. Por fim, concluímos que o jornalismo literário permite não só situar o jornalismo no circuito da comunicação, mas também, e de forma ampliada, estender o circuito da comunicação à sua dimensão cultural, em seu papel pedagógico relevante para qualquer área do conhecimento. Este artículo busca situar el periodismo literario como disciplina de saberes complejos y transdisciplinarios, necesaria para la formación de todo periodista. Se trata de entender y de integrar la práctica de narrar los problemas de los niveles de realidad. Los conceptos de literatura de complejidad y de transdisciplinariedad sirven de base a nuestra reflexión. Con el conto “Com o vaqueiro Mariano”, traemos la literatura de João Guimarães Rosa y sus relaciones con los saberes periodísticos, desde la noción de entrevista, pasando por el sistema de producción y circulación de la información hasta las técnicas de escrutinio que el autor empleaba. Por último, concluimos que el periodismo literario permite no sólo situar el periodismo en el circuito de la comunicación, sino también, y de forma ampliada, extender el circuito de la comunicación a su dimensión cultural, ejerciendo tal disciplina un papel pedagógico relevante para cualquier área del saber.